Desafios do ensino médio no projeto político pedagógico na perspectiva de educação integral - Silva, Antonio Torquato da (2017)
This research aims at analysing the identified challenges of high school in the pedagogical political Project (PPP) of a public school in the State of São Paulo in order to highlight events in the same, pointing to the development of integral education3. The harmony in interpersonal relationships, engendered from inclusive educational environments, provide civility, respect, tolerance and altruism, which are qualities of a just and virtuous society. In this context, in the everyday life of schools the micro and macro actions developed by all members of the school community are highlighted, as well as the respect for differences and the recognition of individual and collective potentialities. In this sense, the reasearch’s proposal is to reflect on the cotributions of the PPP, as the primary tool that schools have to promote a collective, fluent and inclusive dialogue, through the construction of a pedagogical work that meets the goals of the school, in a dialogical way with community, in the perspective of integral education which aims at the full development of the intelectual, cognitive, physical, emotional, social and ethical dimensions of adolescents and young people. To this end, doctumentary and bibliographical searches were carried out so that there is better understanding of reality. The research investigates the characteristics of high school organization in PPP; the respect for the students of the School of Young People4 represented by adolescents and young people of the 21st century; and if the education which adolescents and young people are receiving points to the offering integral education. The research shows that the PPP by articulating with the reality of school everyday life towards the development of integral education, it extends and develops the potentialities of adolescents and young people in the perspective of forming a full citizen of duties and rights 3 Education which forms the citizen in the various and different dimensions of knowledge, it is to train someone to the acquisition of intelectual, cognitive, physical, emotional, social and ethical autonomy, it is to train individuals full of skills and competences to the exercise of their duties and rights in an ethical, responsible and sympathetic way, and above all, with humanism. 4 Pseudonym of the school resarched